EVALUATION OF THE APPLICATION OF THE COOPERATIVE LEARNING MODEL READING INTEREST OF RECIPROCAL TEACHING TYPE STUDENTS - Maru’ao, Eber Felora; Bawamenewi, Arozatulo; Halawa, Sunida; Buulolo, Yustina (Universitas Islam Raden Rahmat Malang, 2024)
Interest in reading is an activity carried out by someone through intention without coercion from anyone to find out the contents of a reading result. This activity can also be done by anyone at any time, whether outside the classroom or in another place. The purpose of this research is to determine the evaluation of the application of the cooperative learning model for students' reading interest in the reciprocal teaching type. This research uses qualitative methods using observation and interview data collection techniques. The research instrument used is conveying learning objectives and motivating students, the second stage is presenting information, the third stage is organizing students into several study groups, the fourth stage is guiding students to study in groups, the fifth stage is conducting evaluations and the sixth stage is giving awards. The research results show an increase in students' interest in reading at junior high schools. In this case the teacher pays more attention to students in learning and can provide encouragement for students to have motivation in learning.